THE EFFECT OF SUSTAINABILITY REPORT DISCLOSURE ON COMPANY FINANCIAL PERFORMANCE - Pratiwi, Adelia Viera; Sulistyowati, Erna (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This research aims to examine the Influence of Sustainability Report Disclosure on Company Financial Performance for companies across various sectors that have successfully entered the List of Rating Asia Sustainability Reporting (ASRRAT) and are listed on the Indonesia Stock Exchange (BEI) during the period 2018-2020. By adhering to the criteria of purposive sampling, data was obtained from 13 companies, which served as the sample, comprising 39 observational data points that met the criteria. The data analysis method employed in this study is Partial Least Square (PLS) regression analysis using Warp PLS software. The hypothesis testing results indicate that Sustainability Report disclosure economic dimension has a positive and significant impact, environmental dimension has a negative and significant impact, social dimension does not have a significant impact on a company's financial performance. Companies must consider the trade-off between social and environmental responsibilities and their financial impact on financial performance